Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the inverse of the logarithmic function [tex]\( f(x) = \log_2 x \)[/tex], we need to understand the concept of inverse functions. The inverse function essentially "reverses" the operation of the original function.
1. Define the function and its purpose:
- The function [tex]\( f(x) = \log_2 x \)[/tex] means finding a power [tex]\( y \)[/tex] (output) such that [tex]\( 2^y = x \)[/tex] (input).
2. Rewrite the function in exponentiation form:
- If [tex]\( y = \log_2 x \)[/tex], this implies that [tex]\( 2^y = x \)[/tex].
3. Solve for the input [tex]\( x \)[/tex] in terms of the output [tex]\( y \)[/tex]:
- To find the inverse function [tex]\( f^{-1}(x) \)[/tex], we need to swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex], and then solve for the new output in terms of the new input.
- Swapping [tex]\( x \)[/tex] and [tex]\( y \)[/tex] gives [tex]\( x = \log_2 y \)[/tex], which means [tex]\( 2^x = y \)[/tex].
4. Writing the inverse function:
- Since [tex]\( 2^x = y \)[/tex], the inverse function [tex]\( f^{-1}(x) \)[/tex] is [tex]\( 2^x \)[/tex].
Hence, the inverse of the function [tex]\( f(x) = \log_2 x \)[/tex] is:
[tex]\[ f^{-1}(x) = 2^x \][/tex]
Therefore, the correct answer is:
[tex]\[ f^{-1}(x) = 2^x \][/tex]
1. Define the function and its purpose:
- The function [tex]\( f(x) = \log_2 x \)[/tex] means finding a power [tex]\( y \)[/tex] (output) such that [tex]\( 2^y = x \)[/tex] (input).
2. Rewrite the function in exponentiation form:
- If [tex]\( y = \log_2 x \)[/tex], this implies that [tex]\( 2^y = x \)[/tex].
3. Solve for the input [tex]\( x \)[/tex] in terms of the output [tex]\( y \)[/tex]:
- To find the inverse function [tex]\( f^{-1}(x) \)[/tex], we need to swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex], and then solve for the new output in terms of the new input.
- Swapping [tex]\( x \)[/tex] and [tex]\( y \)[/tex] gives [tex]\( x = \log_2 y \)[/tex], which means [tex]\( 2^x = y \)[/tex].
4. Writing the inverse function:
- Since [tex]\( 2^x = y \)[/tex], the inverse function [tex]\( f^{-1}(x) \)[/tex] is [tex]\( 2^x \)[/tex].
Hence, the inverse of the function [tex]\( f(x) = \log_2 x \)[/tex] is:
[tex]\[ f^{-1}(x) = 2^x \][/tex]
Therefore, the correct answer is:
[tex]\[ f^{-1}(x) = 2^x \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.